The vital role of inpatient rehabilitation facilities in a large health system: The COVID-19 pandemic - Carolin Dohle; Mooyeon Oh-Park; Andrew Gitkind; Jeffrey Menkes; Matt Bartels (The Journal of the International Society of Physical and Rehabilitation Medicine, 2020)
The current COVID-19 pandemic has put the global health-care system into an unprecedented crisis, leaving hospitals overwhelmed and desperate for additional capacity. As of April 20th, 2020, New York State had the most COVID-19 cases in the US. We here describe the process of transforming our freestanding rehabilitation hospital to help to create additional capacity for our parent system, the Montefiore Health System. This transformation required creating a capacity to handle an increased number of patients with higher medical complexity. The sequence of steps taken at Burke Rehabilitation Hospital to rise to the challenge is outlined in this article.